Isolation of canine adipose‐derived mesenchymal stem cells from falciform tissue obtained via laparoscopic morcellation: A pilot study. (20th June 2019) - DePompeo, Christine M.; Giassetti, Mariana Ianello; Elnaggar, Mahmoud M.; Oatley, Jon M.; Davis, William C.; Fransson, Boel A.
Abstract: Objective: To evaluate the feasibility of stem cell isolation from falciform fat harvested via laparoscopic morcellation. Study design: Pilot study. Animals: Eleven client‐owned dogs. Methods: Falciform was harvested traditionally via laparotomy and laparoscopically via tissue morcellation. Harvested tissue was processed with a commercially available adipose tissue dissociation kit to obtain a stromal vascular fraction (SVF). Cells were subsequently labeled for CD90, CD45, and CD44 cell surface antigens by using magnetic‐activated cell sorting (MACS) and fluorescence‐activated cell sorting flow cytometry. CD90 + cells were quantitated, and their viability was assessed with a hemocytometer and a trypan blue exclusion test of cell viability. Results: No perioperative complications occurred in dogs undergoing laparoscopic morcellation. Laparoscopically and traditionally harvested samples yielded an average of 0.39 (±0.1) × 10 6 and 0.33 (±0.1) × 10 6 CD90 + cells, respectively, per 10 million SVF cells. CD90 + cell viability after MACS was 89% (±11%) for morcellated and 86% (±7%) for traditionally harvested samples. Neither CD90 + cell quantity nor viability was different between samples obtained via traditional laparotomy vs laparoscopic morcellation ( P = .38 and P = .63, respectively). Populations of CD90 + cells isolated with each harvest technique had similar CD44 and CD45 expression profiles. Conclusion: Viable populations of CD90 + cells with similar CD44/CD45 expression profiles were isolated from laparoscopically morcellated and traditionally harvested falciform tissue. No appreciable morbidity was associated with laparoscopic falciform morcellation. Clinical significance: Laparoscopic morcellation is a safe and effective minimally invasive approach to falciform tissue harvest for adipose‐derived mesenchymal stem cell isolation.